2021
DOI: 10.1186/s12864-021-07512-6
|View full text |Cite
|
Sign up to set email alerts
|

Telomere-to-telomere assembly of the genome of an individual Oikopleura dioica from Okinawa using Nanopore-based sequencing

Abstract: Background The larvacean Oikopleura dioica is an abundant tunicate plankton with the smallest (65–70 Mbp) non-parasitic, non-extremophile animal genome identified to date. Currently, there are two genomes available for the Bergen (OdB3) and Osaka (OSKA2016) O. dioica laboratory strains. Both assemblies have full genome coverage and high sequence accuracy. However, a chromosome-scale assembly has not yet been achieved. Results Here, we present a chr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 70 publications
2
49
0
Order By: Relevance
“…several different tunicate lineages, including a chromosomal level assembly of O. dioica (Bliznina et al, 2021). Sequencing of two C. intestinalis Type B (i.e., C. intestinalis rather than C. robusta) genomes revealed that between and even within Ciona species, there have been many chromosomal inversions and there are high levels of polymorphism (Satou et al, 2021).…”
Section: Invertebrate Chordate Modelsmentioning
confidence: 99%
“…several different tunicate lineages, including a chromosomal level assembly of O. dioica (Bliznina et al, 2021). Sequencing of two C. intestinalis Type B (i.e., C. intestinalis rather than C. robusta) genomes revealed that between and even within Ciona species, there have been many chromosomal inversions and there are high levels of polymorphism (Satou et al, 2021).…”
Section: Invertebrate Chordate Modelsmentioning
confidence: 99%
“…The peculiar structural and evolutionary characteristics of OdiMTs together with the high evolutionary rate of O. dioica (Denoeud et al, 2010;Berna et al, 2012;Berna and Alvarez-Valin, 2014), and significant level of sequence variation detected between O. dioica populations (Wang et al, 2015(Wang et al, , 2020Bliznina et al, 2021), prompted us to investigate the OdiMT sequences in several O. dioica populations worldwide distributed. We analyzed the MT sequences from animals from Norway (NOR), Oregon (ORE), Japan (Japanese specimens were from two different localizations, Osaka (OSA) and Okinawa (OKI), and we have analyzed FIGURE 3 | Deconvoluted ESI-MS spectra recorded at pH 7.0 (A,B,E,F) and pH 2.4 (C,D,G,H) of OdiMT2 constructs 2.1 (A-D) and 2.2 (E-H) bioproduced with Zn (A,C,E,G) or Cd (B,D,F,H).…”
Section: Genetic Variation In O Dioica Mtsmentioning
confidence: 99%
“…Second, we have shown a direct relationship between the number of the t-12C/12C domain repeats and the metal-binding capacity of OdiMTs. Finally, taking advantage of the high level of genetic variation among O. dioica populations (Wang et al, 2020;Bliznina et al, 2021), we have detected population variants of OdiMT2 with changes in their number of t-12C/12C domains. Our data expose a high structural plasticity of MTs in O. dioica that, as if it was a natural test-bench, seems to be exploring the chordate limits of MT modularity.…”
Section: Introductionmentioning
confidence: 99%
“…Sex chromosomes are «heteromorphic» or differentiated when the X and the Y have different morphologies and genetic content, and «homomorphic» when they are morphologically indistinguishable. Sex chromosomes are present in many invertebrate species such as the sea urchin Paracentrotus lividus, the coral Corallium rubrum, the only non-bilaterian species for which GSD has been described so far [60,61], or Oikopleura dioica, the only gonochoric species among tunicates [62]. In other groups, such as Lepidoptera or parasitic flatworms from the genus Schistosoma, sex is determined by a ZW system, with ZZ individuals being males and ZW (or Z0) individuals being females.…”
Section: Genetic Sex Determination System (Gsd): Sex Determined At Fertilization 221 Sex Chromosomesmentioning
confidence: 99%